Transitivity in social work reports: A case of destitution reports written by professional social workers in Botswana (JULACE: Journal of the University of Namibia Language Centre, 2023)
Social work in Botswana is a rapidly developing profession. In the last fifty or so years, the role of the social worker has changed, from distributing practical help to taking on roles that were previously filled via age- and status-based social structures. A lot of research has been done on business communication in different workplaces. However, there is not much done on Social work professional communication in Botswana. This study, which is part of a longer study, analysed the types of texts produced by social workers in their professional settings. The research method for this study combines two major research tools in the qualitative inquiry, which are text analysis and interviews. Sixty-four (64) destitution reports were collected and analysed. Six (6) professional social workers were also interviewed to share their experiences in writing the reports. The findings show the powers that the social workers have over their clients.